Can health-insurance help prevent child labor? An impact evaluation from Pakistan - Landmann, Andreas; Froelich, Markus (Journal of Health Economics, 2015)
Child labor is a common consequence of economic shocks in developing countries. We show that reducing vulnerability can affect child labor outcomes. We exploit the extension of a health and accident insurance scheme by a Pakistani microfinance institution that was set up as a randomized controlled trial and accompanied by household panel surveys. Together with increased coverage the microfinance institution offered assistance with claim procedures in treatment branches. We find lower incidence of child labor, hazardous occupations and child labor earnings caused by the innovation. Boys are more often engaged in child labor in our sample, but also seem to profit more from the insurance innovation.
Created from Fastlane, Scopus look-up
Keywords: Child labor; Health insurance; Microinsurance; Pakistan; Vulnerability